2005
DOI: 10.1111/j.1742-4658.2005.04894.x
|View full text |Cite
|
Sign up to set email alerts
|

Light‐harvesting complex II protein CP29 binds to photosystem I of Chlamydomonas reinhardtii under State 2 conditions

Abstract: Excitation of the membrane-bound protein complexes photosystem I (PSI) and II (PSII) by light must be optimized to ensure the highest efficiency of photosynthetic electron transport. Redistribution of excitation energy between both photosystems as an immediate and dynamic response to changing illumination conditions occurs during the process termed 'State transitions', where State 1 is induced by excess PSI light and State 2 by excess PSII light [1]. State 1 to State 2 transition occurs in response to the redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
141
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(151 citation statements)
references
References 37 publications
9
141
1
Order By: Relevance
“…Genetic studies suggest that PsaH, PsaL, and PsaK play important roles in this process (Scheller et al, 2001;Zhang and Scheller, 2004). Electron microscopy studies have identified the binding site of the additional antennae complexes along the PsaL/PsaH-PsaK side (Kargul et al, 2005;Kouril et al, 2005). A new chlorophyll bound by PsaH was identified at the current resolution.…”
Section: Structure Determinationmentioning
confidence: 77%
See 1 more Smart Citation
“…Genetic studies suggest that PsaH, PsaL, and PsaK play important roles in this process (Scheller et al, 2001;Zhang and Scheller, 2004). Electron microscopy studies have identified the binding site of the additional antennae complexes along the PsaL/PsaH-PsaK side (Kargul et al, 2005;Kouril et al, 2005). A new chlorophyll bound by PsaH was identified at the current resolution.…”
Section: Structure Determinationmentioning
confidence: 77%
“…Under state II conditions, PSI associates with a mobile pool of the LHCII antennae, which increases its absorbance cross-section (Kargul et al, 2005;de Bianchi et al, 2010). Genetic studies suggest that PsaH, PsaL, and PsaK play important roles in this process (Scheller et al, 2001;Zhang and Scheller, 2004).…”
Section: Structure Determinationmentioning
confidence: 99%
“…However, we did not detect any projections over and above the classic LHCI⅐PSI supercomplex, suggesting that in maize, LHCII remains associated with the PSII core. It cannot be excluded, however, that a subfraction of mobile LHCII may transiently associate with PSI but it is displaced following the detergent treatment, as previously reported (60,61). To explore this possibility, further investigation is required using digitonin solubilization, an approach that has successfully been used to identify a labile LHCII⅐LHCI⅐PSI supercomplex in the membranes of a C 3 plant, Arabidopsis thaliana (60).…”
Section: Discussionmentioning
confidence: 99%
“…Thylakoid membranes from MS and BS chloroplasts (0.8 mg/ml Chl) were solubilized with 0.9% DDM and fractionated by centrifugation on continuous sucrose density gradients, as detailed previously (61). Protein analyses were conducted using an SDS-PAGE Tris-Tricine system described by Schägger and von Jagow (32).…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, to increase the excitation level in PSI, a certain number of LHCII (including minor LHCII) need to migrate from the aggregated structure (Fig. 5C) to the stroma lamellae (non-appressed region) and reassociate with PSI (12,34,35), thereby completing the state 2 transition (Fig. 5D).…”
Section: Discussionmentioning
confidence: 99%